2013
DOI: 10.1016/j.chroma.2013.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of mass spectral matching-based compound identification in gas chromatography–mass spectrometry

Abstract: Compound identification in gas chromatography–mass spectrometry (GC-MS) is usually achieved by matching query spectra to spectra present in a reference library. Although several spectral similarity measures have been developed and compared using a small reference library, it still remains unknown how the relationship between the spectral similarity measure and the size of reference library affects on the identification accuracy as well as the optimal weight factor. We used three reference libraries to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 12 publications
2
74
0
Order By: Relevance
“…According to the literature, Pearson's correlation coefficient has wide applications for pattern recognition in analytical chemistry, for example, comparative analysis of mass spectral similarity in gas chromatography-mass spectrometry (20). In statistics, Pearson's correlation coefficient, commonly represented by the letter r, is a measure of the strength and direction of the linear relationship between two variables.…”
Section: Data Treatmentmentioning
confidence: 99%
“…According to the literature, Pearson's correlation coefficient has wide applications for pattern recognition in analytical chemistry, for example, comparative analysis of mass spectral similarity in gas chromatography-mass spectrometry (20). In statistics, Pearson's correlation coefficient, commonly represented by the letter r, is a measure of the strength and direction of the linear relationship between two variables.…”
Section: Data Treatmentmentioning
confidence: 99%
“…11 In this study, we perform compound identification using both mass spectrum and retention index information. Therefore, we first studied the performance of the four mass spectral similarity measures in identifying compounds for each of the three query datasets constructed using the method described in the section of Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
“…Several mass spectral libraries have been generated, 1-4 and various mass spectral similarity measures have been developed, including composite similarity, 5 probability-based matching system, 6 Hertz similarity index, 7 normalized Euclidean and absolute value distance, 8 wavelet and Fourier transform-based composite similarity, 9 partial and semi-partial correlations-based composite similarity. 10 Most recently, Koo et al 11 compared the performance of several spectral similarity measures and concluded that the performance compound identification depends on multiple factors including the mass spectrum library, spectral similarity measure and weight factors. They further discussed that the compound identification based on mass spectra only has limited accuracy and the high accuracy compound identification can be achieved by incorporating compound separation information into mass spectrum matching.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple mass spectral similarity measures have been proposed, including composite similarity [1], wavelet transform-based composite measure [2], mixture partial and semi-partial correlation [3]. Some efforts have been also devoted to find the optimal weight factors to improve the identification accuracy [4,5]. The performance of mass spectral matching can be affected by many factors such as the reference spectral library, spectral similarity measure and the weight factors [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Some efforts have been also devoted to find the optimal weight factors to improve the identification accuracy [4,5]. The performance of mass spectral matching can be affected by many factors such as the reference spectral library, spectral similarity measure and the weight factors [4,5]. Furthermore, the mass spectrum matching-based compound identification cannot differentiate the isomers from each other.…”
Section: Introductionmentioning
confidence: 99%